1978
DOI: 10.1107/s0567740878006093
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and melting points of saturated triglycerides in the β-2 phase

Abstract: Abstract. C8N2C12F4, FW 271.0; monoclinic, P2 I, a = 11-925 (2), b= 5.523 (1), c= 6.785 (1) A, fl=95.09 (2) ° (20°C). Z = 2, Dx= 2.02 g cm -3. The final R index was 5.2% (weighted R 4.0%). No absorption correction was applied (/~= 7.84 cm~). Substantial deformation of the parent 2,7-naphthyridine skeleton results because of the short CI-C1 distance (2.307 A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 2 publications
5
27
0
Order By: Relevance
“…The monoacid (n n n) class of TAGs has been studied in most detail, using single-crystal data (n = 10, Jensen & Mabis, 1966;n = 12, Larsson, 1965;Gibon et al, 1984; n = 16, van Langevelde et al, 1999) as well as high-resolution synchrotron powder diffraction (HR-SPD) data (n = 14, 18; van Langevelde et al, 2001a; n = 13, van Langevelde et al, 2001b;n = 15, 17, 19;Helmholdt et al, 2002) and confirmed earlier postulations of the packing of this type of polymorph (Lutton, 1971(Lutton, , 1972de Jong & van Soest, 1978). The singlecrystal packing of the (n n n) analogue EEE 1 (Culot et al, 2000) is also in accordance with this result.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…The monoacid (n n n) class of TAGs has been studied in most detail, using single-crystal data (n = 10, Jensen & Mabis, 1966;n = 12, Larsson, 1965;Gibon et al, 1984; n = 16, van Langevelde et al, 1999) as well as high-resolution synchrotron powder diffraction (HR-SPD) data (n = 14, 18; van Langevelde et al, 2001a; n = 13, van Langevelde et al, 2001b;n = 15, 17, 19;Helmholdt et al, 2002) and confirmed earlier postulations of the packing of this type of polymorph (Lutton, 1971(Lutton, , 1972de Jong & van Soest, 1978). The singlecrystal packing of the (n n n) analogue EEE 1 (Culot et al, 2000) is also in accordance with this result.…”
Section: Introductionsupporting
confidence: 70%
“…The stepless terrace structure of the (n n þ 2 n þ 2)-type TAGs has been proposed by de Unit-cell dimensions as a function of the cell volume. Jong & van Soest (1978) as one of the two packing possibilities according to their -2 packing theory.…”
Section: The Packing Of Lmm and Pssmentioning
confidence: 99%
See 1 more Smart Citation
“…In our investigations of binary triglyceride mixtures (Precht & Greiff, 1978), we were able to establish the existence of larger quantities of the fliv form. The results of de Jong & van Soest (1978), as well as the occurrence of flxv reflections of relatively high intensity in our X-ray diffraction patterns, has induced us to undertake a study on the various arrangements existing for the fin modifications of triglycerides.…”
Section: Introductionmentioning
confidence: 98%
“…Larsson, 1964;Jensen & Mabis, 1966), which we designated as the tim form -the molecules are arranged head-to-head with the two equivalent fatty-acid chains in the so-called 2 position. A report by de Jong & van Soest (1978) further includes in a model relative shifts of monomolecular layers. In our investigations of binary triglyceride mixtures (Precht & Greiff, 1978), we were able to establish the existence of larger quantities of the fliv form.…”
Section: Introductionmentioning
confidence: 99%